Enhanced Two‐Photon‐Pumped Emission from In Situ Synthesized Nonblinking CsPbBr3/SiO2 Nanocrystals with Excellent Stability. Issue 3 (27th December 2017) - Hu, Zhiping; Liu, Zhengzheng; Bian, Yao; Li, Shiqi; Tang, Xiaosheng; Du, Juan; Zang, Zhigang; Zhou, Miao; Hu, Wei; Tian, Yuxi; Leng, Yuxin
Abstract: Perovskites have emerged as a class of cutting‐edge photovoltaic and light‐emitting materials. However, poor stability due to high moisture sensitivity and undesirable blinking severely limits their further application. Here, to solve these problems without destroying optoelectronic performance, a simple process for the fabrication of nonblinking CsPbBr3 quantum dots (QDs) is investigated. By embedding CsPbBr3 QDs into waterless silica spheres, the blinking of QDs can be strikingly suppressed, with an effective improvement of the moisture resistance and enhanced photostability. The silica sphere can also prevent anion exchange of different halide elements between perovskite QDs. Ultrastable amplified spontaneous emission (ASE) from QDs/SiO2 with no degradation for at least 12 h is observed under continuous laser irradiation (4 × 10 7 continuous intense laser shots), with almost no ASE degradation evident after 60 d of storage under ambient conditions. Most notably, the ASE threshold ( P th ) of CsPbBr3 QDs is decreased by 50% and the relative efficiency increased by 388%. The perovskite QDs coated by the waterless SiO2 shell provide a novel platform for realizing perovskite nanomaterials with improved operational stability, nonblinking properties, and enhanced emission all at the same time, which is especially attractive for photovoltaic and light‐emitting device applications. Abstract : To enhance the stability of perovskite quantum dots, a silica sphere is used as a shell by in situ fabrication without water. The embedding of quantum dots in the silica sphere leads to the observation of enhanced amplified spontaneous emission under one‐ and two‐photon excitation. Moreover, the blinking phenomenon characteristic of perovskite nanocrystals is also suppressed.